Effect of Mn content on electrochemical performance and energy density of LiFe1-xMnxPO4/C. (February 2022) - Wang, Li; Li, Yin; Dai, Yongnian; Yao, Yaochun; Zhang, Keyu
Abstract: In this work, LiFe1-x Mnx PO4 /C (x = 0, 0.2, 0.5) composite materials are synthesized to obtain high energy density lithium ion battery cathode materials. The prepared materials were characterized by XRD, XPS, SEM, TEM, CV, EIS and galvanostatic charge-discharge testing. The effect of the Mn content on the structure, morphology and electrochemical performance of LiFe1-x Mnx PO4 /C is studied in detail. It is found that LiFe0.5 Mn0.5 PO4 /C not only possesses the highest specific energy, but also has the best rate performance. The discharge capacities at 5C of LiFe1-x Mnx PO4 /C (x = 0, 0.2, 0.5) are 97.2, 98.8, 107.8 mAh g −1, and the specific energies are 235.0, 248.5 and 299.3 Wh kg −1, respectively. It is calculated that LiFe0.5 Mn0.5 PO4 /C has the highest conductivity and lithium ion diffusion coefficient because of its dispersed particle state and suitable carbon layer thickness. The analysis of the influence of different Mn contents on the electrochemical performance and energy density of LiFe1-x Mnx PO4 /C solid solution materials carried out based on the difference in material structure and morphology provides guidance for the subsequent research and industrial production of these materials. Highlights: The morphology of LiFe1-x Mnx PO4 /C changes with the value of X, which affects the electrochemical performance. LiFe0.5 Mn0.5 PO4 /C shows the highest energy density due to its excellent electrical conductivity. The increase in conductivity is based on batter particle dispersion.